111k views
1 vote
F (0) = -3x + 7 What is the answer?

F (0) = -3x + 7 What is the answer?-example-1

2 Answers

6 votes

Hello!

To solve the function operation, plug in 0 for x, and then solve:


\begin{aligned} \sf{f(0)=-3(0)+7} \\\sf{=0+7\twoheadleftarrow anything \ times \ 0 \ is \ 0. }\\\sf{=7}\end{aligned}

Therefore
\sf{f(0)=7}.

Hope that helps! :)

-art lover

User Svural
by
6.5k points
5 votes

Answer:

f(0) = 7

Explanation:

Substitute x = 0 in the function.

f(x) = -3x + 7

f(0) = -3*0 + 7

= 0 + 7

= 7

User Vasily Kabunov
by
4.6k points